GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG IMUNISASI LENGKAP PADA BALITA DI WILAYAH PUSKESMAS BAYAN KECAMATAN BAYAN KABUPATEN PURWOREJO - Puspa Kusumaningsih, Tri; Rahmah X, Dinda; Septina H.A, Irma (Jurnal Komunikasi Kesehatan, 2025)
WHO stated that in 2021, as many as 25 million children did not receive completeimmunization globally. This data represents 5.9 million more than in 2019 and the highestnumber since 2009. Meanwhile, in Indonesia, the number of children who were not fullyimmunized from 2017 to 2021 is 1,525,936 children (Ministry of Health, 2023). Based ona preliminary study conducted from July to December 2024, there were 105 toddlers whowere immunized at the Bayan Health Center in Purworejo Regency. From interviews with10 mothers of infants, 3 respondents were already aware of complete immunization fortoddlers, 2 respondents had some knowledge, and 5 respondents did not have enoughknowledge. The purpose of this study was to obtain an overview of the level of maternalknowledge regarding complete immunization for toddlers (0-5 years) at the Bayan HealthCenter in Bayan District, Purworejo Regency. This research method is descriptive, usinga cross-sectional approach. The population in this study consisted of mothers who hadtoddlers aged 0-5 years (51 individuals), and the sample in the study was total sampling (51 respondents). The research data were processed using percentage techniques withthe help of SPSS 17, presented in the form of frequency distribution. The research wasconducted from June to December 2024. The study's findings indicated that a majority ofrespondents had a good knowledge level regarding complete immunization for toddlers(45.1%), while some had a sufficient knowledge level (39.2%) and a minority werelacking (15.7%). The findings of this research indicate that the majority of participantsat Bayan Health Center, Purworejo Regency are aware of comprehensive immunizationfor young children. All mothers with toddlers are anticipated to consistently seekinformation regarding immunization and its application. Health workers consistentlyenhance optimal immunization services within the community